2019
DOI: 10.1002/rth2.12202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prophylaxis on health‐related quality of life of boys with hemophilia: An analysis of pooled data from 9 countries

Abstract: Background Prophylaxis reduces the frequency of bleeds in boys with severe hemophilia and is the standard care for their management in resource‐abundant countries. The effect of prophylaxis on Health‐Related Quality of Life (HRQoL) has not been established, because the sample sizes of most studies are too small to explore the relationship of multiple factors that influence HRQoL. Methods The aim of this study was to assess the impact of hemophilia severity and treatment regimen on HRQoL and to establish the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…No relationship was found between bleed rates postswitch and changes in CHO‐KLAT scores. In fact, the 10 boys who showed a reduction in their AJBR showed a small but not statistically or clinically significant reduction in mean CHO‐KLAT scores from 78.6 preswitch to 73.9 postswitch ( P = .15), while parent proxy‐reported CHO‐KLAT scores fell slightly from 81.4 preswitch to 79.9 postswitch ( P = .71).…”
Section: Resultsmentioning
confidence: 92%
“…No relationship was found between bleed rates postswitch and changes in CHO‐KLAT scores. In fact, the 10 boys who showed a reduction in their AJBR showed a small but not statistically or clinically significant reduction in mean CHO‐KLAT scores from 78.6 preswitch to 73.9 postswitch ( P = .15), while parent proxy‐reported CHO‐KLAT scores fell slightly from 81.4 preswitch to 79.9 postswitch ( P = .71).…”
Section: Resultsmentioning
confidence: 92%
“…71.7 (13.1), respectively), whereas increased disease severity was associated with signi cantly lower HRQoL compared to mild or moderate disease. 41 Mean CHO-KLAT score (SD) of Canadian boys was 75.0 (13.0). 41 A CUA comparing primary prophylactic treatment with on-demand treatment in Canadian boys with severe hemophilia A, found that HRQoL and clinical outcomes are substantially improved with prophylaxis compared to on-demand treatment, but it comes at a substantial incremental cost per QALY.…”
Section: Discussionmentioning
confidence: 96%
“…41 Mean CHO-KLAT score (SD) of Canadian boys was 75.0 (13.0). 41 A CUA comparing primary prophylactic treatment with on-demand treatment in Canadian boys with severe hemophilia A, found that HRQoL and clinical outcomes are substantially improved with prophylaxis compared to on-demand treatment, but it comes at a substantial incremental cost per QALY. 42 In a prior study it was not found that prophylactic treatment improved HRQoL, but there were several limitations noted, including not taking into account the impact of frequent intravenous infusions on HRQoL.…”
Section: Discussionmentioning
confidence: 96%
“…Prophylactic factor replacement is a well-established standard of care for patients with severe haemophilia A, 1,2 and routine prophylaxis with factor VIII (FVIII) has been shown to reduce the frequency of bleed episodes, prevent joint damage and improve health-related quality of life. 3,4 However, optimal prophylaxis with conventional FVIII products requires frequent intravenous injections, a substantial burden that can negatively impact treatment adherence. 5 Several strategies have been employed to extend the half-life of FVIII in recombinant FVIII (rFVIII) products, thereby reducing the frequency of infusions.…”
Section: Introductionmentioning
confidence: 99%